Antioxidant Activity Test of Combination of Butterfly Pea Flower Extract (Clitoria ternatea L.) and Ashoka Leaves (Ixora coccinea L.) Using DPPH Method - Safitri, Indah; Suswidiantoro, Vicko; Pratiwi, Mida; Dwiningrum, Riza (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Excess free radicals trigger oxidative stress that accelerates skin aging and increases the risk of degenerative diseases. Efforts to counter it require safe and effective antioxidants based on natural ingredients. Telang flowers (Clitoria ternatea L.) and asoka leaves (Ixora coccinea L.) are known to be rich in flavonoids and phenolates, but data on the effectiveness of the combination of the two are limited. This study aims to assess the antioxidant activity of the mixture of the extracts of the two plants. Ethanol extracts of telang flowers and asoka leaves are prepared, the yield is determined, then phytochemical screening confirms the presence of alkaloids, flavonoids, saponins, and tannins. Anti-radical activity was tested by the DPPH method at three ratios (25 %:75 %, 50 %:50 %, 75 %:25 %) and compared with quercetin (2–10 ppm) as a positive control. The value of IC₅₀ is calculated through linear regression. The 50%:50% mixture showed the highest potency (IC₅₀ = 2.3237 ppm) and was classified as "very strong", close to quercetin (0.7631 ppm) and much better than each of the single extracts reported in the previous study (IC₅₀ telang flower 32.23 ppm; asoka leaf 150.12 ppm). These results indicate a synergy between the two bioactive compounds in simplicia in neutralizing free radicals. Conclusion: the combination of telogen flower–asoka leaf extract has the potential to be developed as a superior natural antioxidant for pharmaceutical or cosmetic products. Further research is recommended to focus on the fractionation of dominant compounds, formulation stability tests, and pre-clinical safety evaluation to in vivo applications.